Os impactos provenientes da adoção de xbrl nos processos de desenvolvimento de software financeiro e nos fatores de qualidade de software - CERQUEIRA, Marcelo Gomes de (2016)
XBRL is currently adopted by various government institutions and companies around the world. Many studies related to its use and benefits for the financial and accounting areas are found in the literature. However, little is known of its benefits for Software Engineering. XBRL can also impact the financial software development processes, as well as in software quality factors. Therefore, there is need to identify the impact from the adoption of XBRL in the development of financial software, but also in software quality factors. This thesis aims to identify the impacts from the adoption of XBRL in financial software development processes and software quality factors. The identification of these impacts will help companies that develop financial software to better understand the advantages related to the use of XBRL, increasing the adoption of XBRL in other companies, which in turn will improve the quality of developed software, facilitating the implementation of quality frameworks within these institutions as well as improving the acceptance of XBRL in software development teams, which have key roles in implementing XBRL.